2005
DOI: 10.1158/1078-0432.ccr-05-0360
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Pharmacodynamics of Highly Schedule-Dependent Agents: Exemplified by Cytarabine-Based Regimens in Acute Myeloid Leukemia

Abstract: Background: Many agents in antineoplastic chemotherapy are highly schedule dependent.Therefore, variables such as total dose and also the area under the curve (AUC) that are schedule insensitive are generally insufficient to adequately represent treatment strength. Purpose: To establish a descriptor of treatment strength that takes into account the differential contribution of plasma concentrations (C) and exposure times (T) towards the cytotoxic effect and to investigate whether such a pharmacodynamically wei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…From these data, the concentration coefficient N for ErPC3 can be determined as 1.9 for HL 60 cells and 1.2 for patient samples, therefore being close to 1 in both settings. Concluding from our experience of ex vivo drug measurement in AML [ 4 , 6 ] exposure concentration as well as exposure time is (almost) equally important for this drug in AML, especially in patient samples. Taking these data into account, the determined LC 50 for HL 60 cells in our study is higher than in previous studies that found the IC 50 for HL 60 cells to be 1.54 μM [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From these data, the concentration coefficient N for ErPC3 can be determined as 1.9 for HL 60 cells and 1.2 for patient samples, therefore being close to 1 in both settings. Concluding from our experience of ex vivo drug measurement in AML [ 4 , 6 ] exposure concentration as well as exposure time is (almost) equally important for this drug in AML, especially in patient samples. Taking these data into account, the determined LC 50 for HL 60 cells in our study is higher than in previous studies that found the IC 50 for HL 60 cells to be 1.54 μM [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the concentration coefficient N is described in detail elsewhere [ 4 ]. In brief, it is based on the finding that the equation C × T = constant ( C = concentration of drug, T = exposure time of the drug) is not sufficient to describe the pharmacodynamic relationship between both parameters for several cytotoxic agents (e.g., cytarabine) to achieve a certain cell kill.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the patients were treated by the "3+7" regimen, three consecutive days of anthracyclines, generally doxorubicin, at 25 mg/m 2 /day on days 1 to 3 given as an intravenous (IV) bolus and continuous IV infusion of cytosine arabinoside 100-200 mg/m 2 over 7 days from days 4 to 10 [17] except AML M3 patients treated by all-trans retinoic acid in addition to chemotherapy [18].…”
Section: Therapeutic Protocolmentioning
confidence: 99%
“…Taken together, cure can be achieved in about 40% of patients, however, with large interindividual variability. publizierten Studien, die randomisiert hochdosiertes Cytarabin mit standarddosiertem Cytarabin in der Induktionstherapie verglichen, hat ein definitiv besseres Ergebnis der Hochdosis hinsichtlich der CR-Raten ergeben [9][10][11][12]; dies konnte durch eine Metaanalyse bestätigt werden [13]. Günstige Effekte finden sich hinsichtlich des Langzeitüberlebens (Tabelle 1).…”
Section: Induktionstherapieunclassified